Perbandingan Gambaran Foto Toraks Antara Pasien Tuberkulosis dengan Diabetes Melitus dan Pasien Tuberkulosis tanpa Diabetes Melitus di RSUP H. Adam Malik Medan - Zikri Putra Lan Lubis; Henny Maisara Sipahutar; Melati Silvanni Nasution; Evo Elidar Harahap; Dedy Dwi Putra; Taufik Ashar (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus (DM) and tuberculosis (TB) have a synergistic effect in worsening the disease severity and treatment outcomes. Chest radiography is the standard imaging modality for TB diagnosis, so identifying characteristic chest radiograph findings has the potential to accelerate early diagnosis and anticipate management in TB patients with and without DM. This study aimed to compare chest x-ray findings between tuberculosis patients with and without DM. This was a cross-sectional study of pulmonary TB patients who underwent posteroanterior (PA) chest x-ray at the Pulmonology Clinic of Haji Adam Malik General Hospital from January 2023 to June 2025. Data were obtained from patient medical records. Bivariate analysis used the chi-square test if the data were normally distributed, or the Fisher exact test if the data were not normally distributed. A p-value <0.05 was considered statistically significant. In TB patients with DM, 81.3% of patients had lesions in the upper lung fields, 65.3% had lesions in the middle lung fields, and 50.7% had lesions in the lower lung fields. The most dominant lesion characteristics were infiltrates (73.3%), fibrosis (42.7%), and consolidation (26.7%). In TB patients without DM, 36% of patients had lesions in the upper lung fields, 29.3% of patients had lesions in the middle lung fields, and 21.3% of patients had lesions in the lower lung fields. The most dominant lesion characteristics were infiltrates (44%), consolidation (25.3%), and fibrosis (18.7%). In TB patients with and without diabetes, the majority of patients had lesions in the upper lung fields, and infiltrates were the most dominant lesion.